A novel angiotensin-I-converting enzyme inhibitory peptide from oyster: Simulated gastro-intestinal digestion, molecular docking, inhibition kinetics and antihypertensive effects in rats - Chen, Hui; Chen, Yu; Zheng, Huizhen; Xiang, Xingwei; Xu, Lu (Frontiers in Nutrition, 2022)
In this study, a novel peptide, AEYLCEAC with high angiotensin-I-converting enzyme inhibitory (ACEI) activity was screened from oyster (Crassostrea gigas) hydrolysates, which was obtained from simulated gastro-intestinal digestion. Candidate peptides were confirmed to have a higher binding to angiotensin-I-converting enzyme (ACE) than the positive drug phosphoinic tripeptide calculated by Discovery Studio, and AEYLCEAC showed the highest ACE inhibition rate in vitro with a IC50 of 4.287 mM. Lineweaver-Burk plots confirmed that the peptidic inhibitory type of ACE is competitive. The molecular docking showed that ACEI activity of the AEYLCEAC was mainly due to the hydrogen bonding interactions with the active pockets (S1 and S2) of ACE. In vivo, AEYLCEAC effectively reduced diastolic blood pressure (DBP) and Systolic blood pressure (SBP) in hypertensive rats. These results indicate that AEYLCEAC might act as a helpful ingredient in functional foods or pharmaceuticals for the prevention and treatment of hypertension.